Accuracy of tissue elasticity measurement using shear wave ultrasound elastography: A comparative phantom study - Ting, C.E.; Yeong, C.H.; Ng, K.H.; Jeet Abdullah, B.J.; Ting, H.E. (2015)
Shear wave elastography (SWE) is an imaging technique using ultrafast ultrasound (20k fps) to measure tissue elasticity. This study aimed to verify the accuracy of SWE measurement compared to the gold standard and investigate the effects of size, depth, stiffness and overlapping of lesions on SWE measurements. A tissue-mimicking phantom with acoustic and shear elasticity properties similar to human breast was developed. The masses’ elasticity was measured using a commercial SWE scanner and an electromechanical microtester (gold standard). Statistically significant difference (p<0.05) was found between the elasticity values measured using SWE and the gold standard, whereby the SWE overes-timated the elasticity by a mean of 22.79±15.00 kPa. This over-estimation might be due to the artefacts caused by wave inter-ferences between the elasticity boundaries. Size and depth of lesions did not affect SWE measurement, however the depth of shear wave detection was limited to 8 cm from the surface.